Description of Drug Storage in Melawai Kemang Pharmacy in 2018 - Nurwulan Adi Ismaya; Nining Prihatin; Okpri Melia; Nur Hasanah (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2021)
Drug management is the most important management in pharmaceutical services at the pharmacy. Drug storage is an inseparable part of all pharmaceutical activities. Pharmacies including pharmacy service facilities, therefore they must be responsible for drug inventory, maintaining drug supplies to avoid damage and maintaining drug quality. Medicines distributed at pharmacies are the same as drugs distributed in hospitals, therefore a good drug storage system at the pharmacy is the same as storing good medicine in hospitals. This type of research is descriptive research with the main purpose of making an objective picture. Data collection is retrospective by observing and reviewing documents following the drug storage indicators by Pudjaningsih. The population of the study were all medicines. Samples were taken based on the total sampling technique. The research instrument is a stock card and the document resulting from stock opname. The conclusion of this research is an overview of drug storage at Melawai Kemang Pharmacy with indicators suitability of stock card is 97,16 %, percentage of drugs expired and or damaged.